4CPS-154 Follow-up in the use of biotherapies in crohn's disease in a french university hospital. (2nd March 2018) - Cortes, B; Micol, M; Esteve, MA; Bertault-Peres, P; Roudot, M
Abstract : Background: Crohn's disease is a chronic inflammatory bowel disease. Treatment of outbreaks is based on corticoids, 5-ASA, nutritional support or anti-TNF alpha therapy (adalimumab, infliximab). The first-line background treatment consists in the use of azathioprine, 6-mercaptopurine and methotrexate. If treatment fails, biotherapies such as anti-TNF alpha or vedolizumab are used. Purpose: The aim of this study is to review the use of biotherapies in Crohn's disease in a French university hospital. Material and methods: Retrospective study of biotherapy prescriptions in Crohn's disease between 1 March 2016 and 1 March 2017: extraction of data from Computerised Physician Order Entry and pharmacy management software (Pharma ®, Computer Engineering). History of patients: recovered by electronic medical records (Axigate ® ). Bibliographical research: Pubmed database, guidelines of French learned societies, French competent authorities and European Crohn's and Colitis Organisation. 1 Results: Between 1 March 2016 and 1 March 2017, 76 patients were treated by a biotherapy for Crohn's disease. Fifty-one patients had 'in-label' prescriptions. Twenty-five patients had 'off-label' prescriptions (increase in infliximab dose or frequency, use of golimumab because of therapeutic failure). The history of 76 patients showed that 43 patients received only one biotherapy since initiation. Thirty-three patients had a switch of biotherapy due to therapeutic failure (66%) or intolerance (34%). First-line patients were treated by infliximab (42), adalimumab (33) and golimumab (one). In the second line, patients were treated by infliximab (16), adalimumab (12), vedolizumab (four) or golimumab (one). In the third line, patients received vedolizumab (six), infliximab (one) and golimumab (one). Conclusion: In this study, infliximab and adalimumab are the most used biotherapies for Crohn's disease in the first line and in the second line as recommended in the European guidelines. 1 'Off label' prescriptions of infliximab follow the French and European guidelines 1 that support an increase in dose or administration frequency to improve pharmacokinetics. Vedolizumab use after failure of anti-TNF therapies, as recommended in European guidelines, is increasing due to its original mechanism of action (anti-integrin antibody). In spite of the therapeutic arsenal, there are still uncontrolled patients. In November 2016, ustekinumab has been approved in France and other drugs are currently in clinical trials. Thus, therapeutic strategy should be updated in the following years. Reference and/or Acknowledgements: 1. Gomollon F, et al. J Crohns Colitis2017Jan;11(1):3–25. No conflict of interest